The fencer [videorecording (DVD)] - Avandi, Märt, 1981-; Ratasepp, Ursula, 1982-; Toompere, Hendrik, 1965- (Music Box Films, 2018)
"Fleeing from the Soviet secret police, Estonian fencer Endel Nelis returns to his homeland and finds work as a children's sports instructor. Quickly becoming a role model to his students, Nelis begins teaching them competitive fencing techniques despite the objections of school administrators. When the children are invited to a fencing tournament in Leningrad, Nelis must make a choice: put his safety first or risk everything to take the children to the competition"--Container.